Deskripsi Kreativitas Anak Di Kelompok B TK Negeri Pembina Ki Hajar Dewantoro I Kecamatan Kota Selatan Kota Gorontalo - Jumiati; Irvin Novita Arifin; Nurul Aini MM Sodik (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to describe the creativity of children in Group B at TK State Pembina Ki Hajar Dewantoro I Kindergarten, Kota Selatan District, Gorontalo City. The research employed a qualitative method focusing on children's creativity in Group B. The study involved 24 children from Group B and one teacher as subjects. Data were collected through interviews and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results revealed that the creativity of children in Group B at TK State Pembina Ki Hajar Dewantoro I Kindergarten, Kota Selatan District, Gorontalo City, could develop optimally based on several indicators. The first indicator, fluency, showed that most children were able to generate numerous ideas quickly and complete specific tasks efficiently. The second indicator, flexibility, indicated that children could create diverse ideas, provide varied answers, and explore alternative solutions. The third indicator, originality, revealed that children could produce unique and unconventional ideas or solutions and solve problems in an original manner. The fourth indicator, elaboration, demonstrated that children could expand their ideas and provide detailed descriptions of an object. The fifth indicator, redefinition, showed that children were capable of revisiting an object and solving problems related to it effectively.